The Oxford Handbook of Spatial Diversity and Business Economics - Andersson, Martin; Karlsson, Charlie; Wixe, Sofia (Oxford University Press, 2025)
For quite some time, research across various fields has highlighted diversity as a critical factor in fostering creativity, knowledge generation, innovation, and entrepreneurship-at the levels of organizations, cities, regions, and entire countries. The aim of this book is to provide a comprehensive overview of the role of diversity in modern advanced economies, appealing to academics, researchers, and advanced students in disciplines such as business, economics, and geography. The volume brings together contributions and perspectives from both economics and business scholars, offering theoretical insights alongside new empirical research that serves as a foundation for policy recommendations. Organized into four parts, the book comprises 16 individual chapters that address the topics of diversity and place development, workforce and labour market diversity, diversity and entrepreneurship, and regional diversity, innovation, and productivity. The introductory chapter complements with a broad discussion on existing research regarding the role of spatial diversity for creativity, knowledge production, innovation, entrepreneurship, and growth in the economy. Throughout the book, diversity is conceptualized as a multi-faceted phenomenon that can be measured and analysed in various dimensions and within different contexts, demonstrating its significant economic impacts at multiple spatial scales.
Publisher Copyright: © The several contributors 2025. The moral rights of the authors have been asserted. All rights reserved.
Keywords: creativity; diversity; entrepreneurship; geography; growth; innovation; knowledge production; labour market; productivity